Implementasi Pola Pendidikan Karakter Pada Anak Berkebutuhan Khusus Di Sekolah Dasar - Rizki Zuliani; Royyan Zam Zam Rachmawati; Hika Yatul Hauliyah (CV. ITTC INDONESIA, 2023)
Character education is an important thing in the educational process in schools. However, character education for children with special needs is often ignored by society. In fact, good character can help children with special needs to be able to overcome the challenges they face and become someone who is more independent. Character education is an important thing in the education process in schools. However, character education for children with special needs is often ignored by society. In fact, good character can help children with special needs to be able to overcome the challenges they face and become someone who is more independent. Character education is an important part of education that aims to shape the personality and morality of students. Character education does not only focus on cognitive aspects/a mental activity that is able to make individuals able to connect, assess and consider an existing event, but also on affective and skill aspects. However, not all students have the same opportunity to get good character education, especially for students with special needs. The research approach used in this research is an action research approach. This approach was chosen because this study aims to improve the quality of the implementation of character education patterns for children with special needs in elementary schools. The action research approach emphasizes the processes of development, implementation, and reflection in the context of actions taken by researchers and research participants. In the action research approach, researchers will work with research participants (teachers and students) to plan, implement, and evaluate actions taken to improve the quality of learning and the application of character education patterns to children with special needs. During the research process, researchers will reflect on the actions that have been taken and make improvements or adjustments needed to achieve the research objectives. It is hoped that the results of this study can make a real contribution in improving the quality of learning and the implementation of character education patterns for children with special needs in elementary schools. From the results of this study, it shows that the pattern of character education applied to children with special needs is very welcome and can assist teachers in educating the character of each student with special needs, where this character education can build character patterns in children or students with special needs. . starting from the pattern of thoughts, behavior, decency, behavior and much more in their character.